2011
DOI: 10.1039/c1cp20814d
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the immobilization process of Au nanoparticles on TiO2(110) by electrostatic interaction between the surface and ionic liquids

Abstract: We found that the adsorption states of Au nanoparticles (NPs) on TiO(2)(110) varied with the ionic liquids (ILs) that encapsulate the NPs during the entire process from synthesis of NPs to immobilization of the NPs on the surface at 323 K. Five kinds of ILs, including three 1-butyl-3-methylimidazolium ([C(4)MIm]) cation-based ILs of tetrafluoroborate ([C(4)MIm][BF(4)]), hexafluorophosphate ([C(4)MIm][PF(6)]) and bis(trifluoromethylsulfonyl)amide ([C(4)MIm][NTf(2)]), and two [BF(4)] anion-based ILs of 1-(methox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…It has already been demonstrated that, depending on sputtering parameters, it is possible to obtain AuNPs of small sizes (1−10 nm) on pure IL, 53−55 pure inorganic oxides (TiO 2 ), 56 and ILs supported on inorganic oxides (ILs dispersed on TiO 2 ). 57 It is also worth noting that, in all cases, the AuNP surface is exclusively composed of metallic gold (Au(0)), as determined by XPS (Figure 1g). Furthermore, there is a positive shift in the Au binding energies (for instance, see Au 4f components in Table 1 and Figure 1 and Au valence band (VB) in Figure S6 in the Supporting Information ) of the AuNPs onto γ-Al 2 O 3 , with respect to those on the IL-hybrid γ-Al 2 O 3 (B1 and B2), suggesting that, in the latter case, the interaction of the AuNPs with the γ-Al 2 O 3 support was decreased by the presence of the IL pair layers.…”
Section: Acs Catalysismentioning
confidence: 85%
See 1 more Smart Citation
“…It has already been demonstrated that, depending on sputtering parameters, it is possible to obtain AuNPs of small sizes (1−10 nm) on pure IL, 53−55 pure inorganic oxides (TiO 2 ), 56 and ILs supported on inorganic oxides (ILs dispersed on TiO 2 ). 57 It is also worth noting that, in all cases, the AuNP surface is exclusively composed of metallic gold (Au(0)), as determined by XPS (Figure 1g). Furthermore, there is a positive shift in the Au binding energies (for instance, see Au 4f components in Table 1 and Figure 1 and Au valence band (VB) in Figure S6 in the Supporting Information ) of the AuNPs onto γ-Al 2 O 3 , with respect to those on the IL-hybrid γ-Al 2 O 3 (B1 and B2), suggesting that, in the latter case, the interaction of the AuNPs with the γ-Al 2 O 3 support was decreased by the presence of the IL pair layers.…”
Section: Acs Catalysismentioning
confidence: 85%
“…Although these IL layers are thin, previous reports on hydrogenation processes described that similar thin IL layers produce the best compromise between the hydrogenation activity and the selectivity enhacement by IL substrate/product discrimination. 55,57,60 These behaviors were ascribed to the effect on the concentration of reactants available at the catalytic center by the distinct reactant solubility/ miscibility in the IL 62−64 or to the IL interaction with specific catalytically active particle sites: i.e., a proposed ligand-like interaction with different surface sites on Pt or PdNPs by the use of the IL 1-n-butyl-3-methylimidazolium bis-(trifluoromethylsulfonyl)imide (BMI•NTf 2 ). 60,62,65 The IL pair interaction with the AuNPs was further confirmed by comparing the XPS spectra of B1, B2, Au/B1, and Au/B2 (see Figure S8 in the Supporting Information).…”
Section: Acs Catalysismentioning
confidence: 99%
“…They further dissolved the Ag nanocubes by chemical etching to create Au/Ag nanocubes and Au nanoframes [157]. The team of Torimoto also showed the adsorption of Au NPs on a TiO 2 (110) substrate with the IL encapsulating the NPs on the TiO 2 surface [180]. Through a post-treatment, they immobilized the Au NPs and removed the IL layers, resulting in self-assembled Au NP arrays on the TiO 2 (110) substrate [180].…”
Section: Nanocomposite Structures 2361 Nanoparticle Stabilization Onto Carbon Nanostructuresmentioning
confidence: 99%
“…Suzuki et al proposed a novel strategy for controlling the adsorption positions of NPs on solid substrates by varying the electrostatic interactions between the substrate surface and the ILs, by using a rutile TiO 2 (110) single crystal surface and Au NPs obtained from liquid medium sputtering [31]. The authors revealed that the combination of a charged surface and charged molecules had the potential to afford control of the NP location on the surface, by tuning the electrostatic interactions.…”
Section: Transfer Of Npsmentioning
confidence: 99%
“…First, metal NP synthesis using ionic liquids will be discussed, which includes the synthesis of single material NPs and the effect of sputtering conditions [19][20][21][22][23][24][25][26][27], various alloying strategies [15,23,24,28], and techniques for transferring synthesized NPs [29][30][31]. Subsequently, we discuss NP synthesis using low-volatile polymers, including the use of thiol compounds and transfer techniques [32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%